Tensile properties of poly lactic acid (Pla) tungsten trioxide (wo3) nano composites for 3d printing process - Shaath M.L.M.; Ansar M.N.M.; Atiqah A.; Hamdan A. (Blue Eyes Intelligence Engineering and Sciences Publication, 2023)
Poly Lactic Acid (PLA) is one of the most crucial aliphatic polyesters which is considered as one of the favourable options in environmentally friendly thermoplastic polymers since it could be biodegraded in certain conditions. PLA has been extensively used in the packaging, electronic industries, and household applications. As a result, the improvement of mechanical properties of PLA is necessary, which can be achieved through heat resistant materials such as Tungsten trioxide (WO3). The objective of this research was to investigate the tensile properties of PLA-WO3. The 3D printing process was employed to fabricate PLA-WO3 (3wt% WO3) and Neat PLA (control sample). The tensile test was conducted to investigate the effect of WO3 to the PLA. The results show that the tensile properties of PLA-WO3 were improved up to 75% as compared to Neat PLA. This result shows positive indication to the PLA-WO3 for many industrial applications. BEIESP.